Author Correction: Sole coloration as an unusual aposematic signal in a Neotropical toad (Scientific Reports, (2019), 9, 1, (1128), 10.1038/s41598-018-37705-1) - Rößler, Daniela C. (2019)
This Article contains errors in the Results section under subheading ‘Visual Modelling’. “For snakes, the visual model did not reveal any significance in terms of chromaticity between red and non-red feet. But, in terms of achromatic information, for the snake the contrast of red feet (11.10 ± 7.94 JND, N = 32) was significantly higher than the contrast of non-red feet (20.86 ± 10.89 JND, N = 20) against foliage background (U = 149, p #x003C; 0.001 two-tailed). Against dorsal dark coloration, the achromatic contrast of red feet (11.10 ± 7.94 JND, N = 32) was significantly smaller than for non-red feet (20.86 ± 10.89 JND, N = 20) (U = 148, p #x003C;0.001 two-tailed).’’ should read: “For snakes, the visual model did not reveal any significance in terms of chromaticity between red and non-red feet. But, in terms of achromatic information, for the snake the contrast of red feet (25.92 ± 7.97, N = 32) was significantly higher than the contrast of non-red feet (18.43 ± 9.29, N = 20) against foliage background (U = 149, p #x003C; 0.001 two-tailed). Against dorsal dark coloration, the achromatic contrast of red feet (11.10 ± 7.94 JND, N = 32) was significantly smaller than for non-red feet (20.86 ± 10.89 JND, N = 20) (U = 148, p #x003C; 0.001 two-tailed).’’. © 2019, The Author(s).